Reversal of pulmonary hypertension in paediatric patients with restrictive cardiomyopathy. (31st May 2021) - Schlein, Johanna; Riebandt, Julia; Laufer, Günther; Zimpfer, Daniel
Abstract: Left ventricular assist devices can reverse pulmonary hypertension in cardiac transplant candidates with heart failure with a reduced ejection fraction. Whether a similar approach is applicable in restrictive cardiomyopathy is uncertain. We report the successful implantation of a Medtronic HVAD left ventricular assist device in a bridge-to-candidacy concept in 2 paediatric patients with restrictive cardiomyopathy. Abstract : Pulmonary hypertension (PH) is frequent in patients with restrictive cardiomyopathy and a contraindication for a cardiac transplant due to the risk of post-transplant failure of the unconditioned right ventricle [1].